Model Pendampingan Masyarakat untuk Peningkatan Kunjungan Wisata di Desa Wisata Kreatif Perdamaian - Rosalina Br. Ginting; Maryanto Maryanto; Suyoto Suyoto; Antono Herry Purnomo Adhi (STIKes Ibnu Sina Ajibarang, 2024)
Desa Wisata Kreatif Perdamaian (DWKP) has the potential to be developed but is constrained by the lack of optimism of tourism actors, tourist attractions that are not attractive to tourists, and the lack of support from the Poncoruso Village community in the development of tourism villages. Community service is aimed at providing solutions related to the problems faced by DWKP. Community service is carried out by providing motivation for managers related to the lack of optimism of tourism actors, encouraging community participation in supporting tourism villages, and strengthening tourism village organizations.